Línguas de imigração em contato com o português no oeste catarinense: crenças e atitudes linguísticas - Hasselstron, Munick Maria (2018)
This dissertation research aims to relate the linguistic beliefs and attitudes of Polish-Brazilian, Italian-Brazilian and German-Brazilian bilinguals to verify similarities and differences in their perceptions and beliefs about their respective minority language. The beliefs about the language are observed based on the answers given to a metalinguistic questionnaire and the linguistic attitudes through the real use of the language, from the kinship terms (sanguineous, alliance and spiritual), aiming to perceive which of the ethnic groups maintain more the minority language. The research is carried out in bilingual contexts in three localities belonging to the state of Santa Catarina: Nova Erechim (Pol.-Pt.-RS), Chapecó (Tal.-Pt.-RS) and São Carlos (Hr.- Pt.-RS) . The first settlers of the three points of the research arrived, respectively, around 1952, 1931 and 1927. Most of the colonists came from the older Rio Grande do Sul colonies, gauchos descendant of Polish, Italian and German immigrants. This research becomes relevant as it deals with minority immigration languages in contact, an indispensable study for the future development of linguistic policies. The study is based on Multidimensional and Relational Dialectology (Thun, 1996, 1998, 2005, 2010), which contemplates the variational space in different dimensions. The data collection and the informants choice is based on the cross model developed by Thun (1996). Thus, this research considers the following dimensions: diatopic (New Erechim, Chapecó and São Carlos), diageracional (GI [from 18 to 36 years] and GII [55 years or more]), diassexual (male and female), diastratic (with full or incomplete graduation) and Cb [no schooling until high school]) and dialingual (Polish, Talian, and Hunsrückisch in contact with Portuguese-Rio Grandense). The research, as well as the questionnaires used to collect data, on both beliefs and the lexical questionnaire on kinship terms, is part of the Atlas of Languages in Contact at the Border - West Catarinense (ALCF-OC) project. Data from the German Minority Linguistic-Contactual Atlas in Bacia do Prata-Hunsrückisch (ALMA-H) are also used. The analysis of the research data leads us to verify that, in the points researched, the immigration variety is maintained more by the German ethnic group and by the Cb and the GII. In São Carlos, a German-Brazilian locality, the German language is still used in some social contexts, in addition to the familiar, whereas in Nova Erechim and in Chapecó, the respective immigration varieties, if used, they are restricted to the family contact. Informants, in general, have expressed positive beliefs about their immigration languages, but they are aware of their low usage, a fact that is noticeable in the language attitudes.